Nanoparticle size-specific actin rearrangement and barrier dysfunction of endothelial cells. Issue 7 (9th August 2017) - Liu, Yizhong; Rogel, Noga; Harada, Kei; Jarett, Leigha; Maiorana, Christopher H.; German, Guy K.; Mahler, Gretchen J.; Doiron, Amber L.
Abstract: In this work, we evaluated the impact of gold nanoparticles on endothelial cell behavior and function beyond the influence on cell viability. Five types of gold nanoparticles were studied: 5 nm and 20 nm bare gold nanoparticles, 5 nm and 20 nm gold nanoparticles with biocompatible polyethylene glycol (PEG) coating and 60 nm bare gold nanoparticles. We found that all tested gold nanoparticles did not affect cell viability significantly and reduced the reactive oxygen species (ROS) level in endothelial cells. Only 20 nm bare gold nanoparticles caused an over 50% increase in endothelial barrier permeability and slow recovery of barrier function was observed after the gold nanoparticles were removed. This impairment in endothelial barrier function was caused by unbalanced forces between intracellular tensions and paracellular forces, actin microfilament rearrangement, which occurred through a Rho/ROCK kinase-dependent pathway and broke the force balance between intracellular tensions and paracellular forces. The size-specific effect of gold nanoparticles on endothelial cells may have important implications regarding the behavior of nanoparticles in the biological system and provide valuable guidance in nanomaterial design and biomedical applications.